Balloon Angioplasty – The Legacy of Andreas Grüntzig, M.D. (1939–1985) - Barton, Matthias; Grüntzig, Johannes; Husmann, Marc; Rösch, Josef (Frontiers in Cardiovascular Medicine, 2014)
In 1974, at the Medical Policlinic of the University of Zürich, German-born physician-scientist Andreas Grüntzig (1939-1985) successfully applied a balloon-tipped catheter to re-open a severely stenosed femoral artery, a procedure which he initially called “percutaneous transluminal dilatation”. Transluminal angioplasty of atherosclerotic vascular disease, for which Grüntzig and Charles T. Dotter (1920-1985) received a nomination for the Nobel Prize in Physiology or Medicine in 1978, became one of the most successful examples of translational medicine in the 20th century. Known today as percutaneous transluminal angioplasty (PTA) in peripheral arteries or percutaneous transluminal coronary angioplasty (PTCA) or percutaneous coronary intervention (PCI) in coronary arteries, balloon angioplasty has become the method of choice to treat patients with acute myocardial infarction or occluded leg arteries. On the occasion of the 40th anniversary of balloon angioplasty, we summarize Grüntzig’s life and career in Germany, Switzerland, and the United States and also review the developments in vascular medicine from the 1890s to the 1980s, including Dotter’s first accidental angioplasty in 1963. The work of pioneers of catheterization, including Pedro L. Fariñas in Cuba, André F. Cournand in France, Werner Forssmann, Werner Porstmann and Eberhard Zeitler in Germany, Sven-Ivar Seldinger in Sweden, and Thomas J. Fogarty, Melvin P. Judkins, Richard K. Myler, Dickinson W. Richards, and F. Mason Sones in the United States, is discussed. We also present quotes and excerpts from a unfinished book manuscript by Grüntzig, statements of his former colleagues and contemporary witnesses, and also include hitherto unpublished historic photographs and links to historic materials and archive recordings. This year, on June 25, 2014, Andreas Grüntzig would have celebrated his 75th birthday. This article is dedicated to his memory.